KEEPING ACCOUNTS WITH CREDITORS IN BUDGET ORGANIZATIONS (Scientific Journal of Actuarial Finance and Accounting, 2025)
Accounting with creditors in budget organizations is an important aspect of financial control and accountability, especially in the conditions of the public sector of Uzbekistan. This article examines the regulatory frameworks, accounting practices and challenges faced by budget organizations in managing creditor relationships. It examines the legal and financial guidelines governing the settlement of accounts with creditors, the role of financial reporting in ensuring transparency, and measures aimed at preventing mismanagement or fraud. The study highlights the importance of sound debt management to maintain fiscal stability and strengthen confidence in public sector financial operations. With a detailed analysis of Uzbekistan's national regulatory and legal documents, financial management systems and practical examples from budget organizations, this article provides insights into best practices and trends in improving the state financial management system.